Responses of urban shallow lakes to early stages of rehabilitation - Zhang, Xiaoju, author; Roesner, Larry A., author; Carlson, Kenneth, author; Liang, Qian, author; Colorado State University, publisher (Colorado State University. Libraries, 2011)
The Fossil Creek Lakes, located in Fossil Creek Community Park in south Fort Collins, Colorado, are the remnants of the old Poertner Reservoir constructed more than 100 years ago, which is an aesthetic and recreational fishing amenity to park visitors. However, the accumulation of 100 years of organic matter and sulfur compounds in the bottom coupled with summer and winter thermal stratification results in extremely low redox potentials in the bottom sediments and high concentrations of reduced sulfur (S-II). The presence of H2S (g), particularly during lake turnover events has resulted in numerous odor complaints from park visitors and residents living nearby. In addition, fish kills occur during the late summer and through the winter, which has forced water managers to look for solutions to eliminate air quality impacts and protect water quality. As maintenance of aerobic conditions in the hypolimnion is an important consideration for successful lake management, this research focused on the use of artificial aeration to increase hypolimnetic dissolved oxygen levels. The number of aerators was substantially less in number than would typically be used in a lake of this size, because it was hypothesized that by placing the aerators in the deeper pockets of the lake, density differences would cause the heavier bottom water to "flow downhill" toward the aerators, increasing the effective circulation cells of the individual aerators. The experimental method involved monitoring of specific water quality constituents prior to and after the aeration. Preliminary findings show the aeration system significantly eliminated summer and winter lake stratification, reduced the odor problems, improved the water quality, including pH, solids, and nitrogen and phosphorus species.
Hydrology days 2011
AGU hydrology days 2011
2011 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2011.